The ECG Characteristics of Patients With Isolated Hypomagnesemia - Yang, Yiheng; Chen, Cheng; Duan, Penghong; Thapaliya, Suman; Gao, Lianjun; Dong, Yingxue; Yin, Xiaomeng; Yang, Xiaolei; Zhang, Rongfeng; Tan, Ruopeng; Hui, Simei; Wang, Yue; et al. (Frontiers in Physiology, 2021)
Background Electrocardiographic (ECG) characteristics of patients with isolated hypomagnesemia are not well defined. We aimed to investigate these ECG characteristics in order to define clearly the features of isolated hypomagnesemia. Hypothesis: Lower serum magnesium could affect ECG parameters after excluding potential confounders Methods This retrospective study was of patients with low serum magnesium<0.65mmol/L compared with the same patients after restoration to normal serum magnesium. Patients with hypokalemia, hypocalcemia and other electrolyte disturbances were excluded. ECG parameters manually determined and analyzed were P wave dispersion, PR interval, QRS duration, ST-T changes, T wave amplitude, T peak-to-end interval (Tpe), corrected Tpe (Tpec), QT, corrected QT (QTc), QT peak corrected (QTpc) and Tpe dispersion, Tpe/QT ratio. Results Two-hundred-and-fourteen patients with isolated hypomagnesemia were identified with 50 of them (56.9±13.6 years; 25 males) being eligible for final analysis from 270997 patients presenting 04.2011-10.2017. In the period of isolated hypomagnesemia, P wave duration was found prolonged (p≤0.02); as was QTc (447.21±33.12ms vs. 438.67±23.12ms, p=0.002). Tpec (128.88±24.00ms vs. 115.21±21.06ms, p=0.000) and Tpe/QT ratio (0.29±0.05 vs. 0.26±0.05, p=0.000) were increased. QTpc decreased during hypomagnesemia (345.40±29.26ms vs.352.94±25.24ms, p=0.001). However, no significant differences were found in PR interval, QRS duration (86.53±12.07ms vs. 88.03±12.27ms, p=0.07) and ST-T segments between the patients and their own controls. Conclusions In patients with isolated hypomagnesemia, P wave duration, QTc, Tpec, and Tpe/QT ratio suggesting (increased ventricular repolarization dispersion) were significantly increased compared with normal magnesium levels in the same patients after restoration of normal magnesium levels.